Data Analysis for Predictive Maintenance of Servo Motors - ATAKÖK, GÜRCAN; GİRİT, OĞUZ; ERSOY, SEZGİN (HINDAWI LTD, 2020)
Vibration and temperature data of a servo motor are analyzed with PLC which is widely used in the industry. With this system, power supply can be detected on the servo motors. In this way, undesirable situations such as disruptions in production and productivity loss can be prevented from occurring. It is an important problem for businesses to detect malfunctions that may occur in servo motor dysfunction. Previously, methods such as ultrasonic sound measurements, thermal cameras, endoscopy equipment, and energy analysis have been used and discussed in the literature. Our study offers a PLC-based vibration and temperature measurement system designed as a solution of this problem. In this system, vibration and temperature measurements were made while the servo motor was kept running. These measurements were measured with or without load, considering the operating ranges of the servo motor, and the compatibility of the data was evaluated.
Keywords: TORSIONAL VIBRATIONS; DIAGNOSIS